Bina Bahasa Inggris Untuk Siswa MTs Muhammadiyah Manado Melalui Kegiatan Daily Conversation - Nagauleng, Andi Mukarrramah; Halimah, Nur; Saini, Fadhlan; Tinangon, Windi Garace (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Manado, 2019)
The purpose of this service is to improve the ability of MTs Muhammadiyah students to master basic English skills for daily communication using the Daily Conversation method. This activity is carried out once a week, starting from 12 August to 30 November 2019, at MTs Muhammadiyah Singkil District, Manado City. The results obtained from the activity are the ability of MTs Muhammadiyah students in daily communication in English has been quite fluent. This method is preferred by students because the material taught is related to expressions used daily. Students are enthusiastic during learning activities, but several things still need to be improved, namely motivation and confidence to use English in daily conversation.